Regulating landfills using measured methane emissions: An English perspective. (15th March 2019) - Bourn, M.; Robinson, R.; Innocenti, F.; Scheutz, C.
Highlights: Methane measurements show that a high proportion of landfill gas can be captured. A methane collection index (MCI) can be calculated from methane measurements. A MCI is a direct measure of landfill gas management performance. The MCI can be used to trigger improvements in landfill gas collection. Abstract: Methane emissions from landfills are an important source of greenhouse gases in the UK and worldwide. This paper considers how measurements of methane emissions could be used to regulate landfills in England in order to reduce the contribution of landfilling to climate change. The paper presents the results of a number of UK studies undertaken to quantify methane emissions from landfills. The methods used have included the DIAL (Differential Absorption Lidar) technique and a tracer gas dispersion method. A method based on aerial measurements has been developed. Methane emission rates were measured at 15 biodegradable waste landfills. All of the landfills where measurements took place had an active landfill gas extraction system. A methane collection index (MCI) is calculated for each landfill using the ratio of the methane collection rate to the sum of the collection and emission rates. The values of the index in the campaigns reported here ranged from 0.28 to 0.90. The modern operational landfills surveyed achieved MCI values with a much narrower range of between 0.64 and 0.90 with an average of 0.76. This has demonstrated that it is possible for these landfills to collect a high proportion of the landfill gas. A proposed approach is presented for regulating landfills using the measured MCI. This would involve an annual measurement campaign to quantify the methane emissions and the use of the data provided by these surveys to develop an achievable but challenging MCI limit. A limit value of 0.75 for the MCI is used to illustrate the approach. An MCI that falls below the limit would trigger actions to reduce the methane emissions from the landfill.